Confirmation and Control of HPPD-Inhibiting Herbicide–Resistant Waterhemp (Amaranthus tuberculatus) in Nebraska. (6th February 2017) - Oliveira, Maxwel C.; Jhala, Amit J.; Gaines, Todd; Irmak, Suat; Amundsen, Keenan; Scott, Jon E.; Knezevic, Stevan Z.
Abstract : Field and greenhouse experiments were conducted in Nebraska to (1) confirm the 4-hydroxyphenylpyruvate dioxygenase (HPPD)-inhibiting resistant-waterhemp biotype (HPPD-RW) by quantifying the resistance levels in dose-response studies, and (2) to evaluate efficacy of PRE-only, POST-only, and PRE followed by POST herbicide programs for control of HPPD-RW in corn. Greenhouse dose-response studies confirmed that the suspected waterhemp biotype in Nebraska has evolved resistance to HPPD-inhibiting herbicides with a 2- to 18-fold resistance depending upon the type of HPPD-inhibiting herbicide being sprayed. Under field conditions, at 56 d after treatment, ≥90% control of the HPPD-RW was achieved with PRE-applied mesotrione/atrazine/ S- metolachlor+acetochlor, pyroxasulfone (180 and 270 g ai ha −1 ), pyroxasulfone/fluthiacet-methyl/atrazine, and pyroxasulfone+saflufenacil+atrazine. Among POST-only herbicide programs, glyphosate, a premix of mesotrione/atrazine tank-mixed with diflufenzopyr/dicamba, or metribuzin, or glufosinate provided ≥92% HPPD-RW control. Herbicide combinations of different effective sites of action in mixtures provided ≥86% HPPD-RW control in PRE followed by POST herbicide programs. It is concluded that the suspected waterhemp biotype is resistant to HPPD-inhibiting herbicides and alternative herbicide programs are available for effective control in corn. The occurrence of HPPD-RW in Nebraska is significant because it limits the effectiveness of HPPD-inhibiting herbicides. Abstract : Se realizaron experimentos de campo y de invernadero en Nebraska para (1) confirmar un biotipo de Amaranthus tuberculatus resistente a inhibidores de 4-hydroxyphenylpyruvate dioxygenase (HPPD) (HPPD-RW) cuantificando el nivel de resistencia con estudios de respuesta a dosis, y (2) evaluar la eficacia de programas de herbicidas para el control de HPPD-RW en maíz con sólo herbicidas PRE, sólo POST, y herbicidas PRE seguidos por POST. Los estudios de respuesta a dosis en invernadero confirmaron que el biotipo de A. tuberculatus en Nebraska ha evolucionado resistencia a herbicidas inhibidores de HPPD con 2 a 18 veces mayor resistencia dependiendo del tipo de herbicida inhibidor de HPPD que se aplicó. Bajo condiciones de campo, a 56 d después del tratamiento, se alcanzó ≥90% de control de HPPD RW con aplicaciones PRE de mesotrione/atrazine/ S -metolachlor + acetochlor, pyroxasulfone (180 y 270 g ai ha −1 ), pyroxasulfone/fluthiacet-methyl/atrazine, y pyroxasulfone + saflufenacil + atrazine. Entre los programas de herbicidas con sólo POST, glyphosate, una premezcla de mesotrione/atrazine mezclados en tanque con diflufenzopyr/dicamba, o metribuzin, o glufosinate brindaron ≥92% control de HPPD-RW. Combinaciones de herbicidas efectivos con diferentes sitios de acción en mezclas brindaron ≥86% de control de HPPD-RW en programas de herbicidas PRE seguidos por POST. Se concluyó que el biotipo de A. tuberculatus es resistente a herbicidas inhibidores de HPPD y que hay programas de herbicidas alternativos disponibles para su control efectivo en maíz. La ocurrencia de HPPD-RW en Nebraska es significativa porque limita la efectividad de herbicidas inhibidores de HPPD.